The king who fooled Hitler [videorecording (DVD)] - Berthon, Simon; Elston, Paul; Elston, Paul; McCrory, Helen (PBS, 2023)
A world scoop about the deception which fooled Hitler about the Normandy landings of 1944. In a tale of double agents and decoys, the investigation reveals, for the first time, the identity of the most secret of them all: George VI, as well as how the royal family managed to lose one of Britain's greatest secrets.